Effects of Telbivudine Treatment on the Circulating CD4+ T-Cell Subpopulations in Chronic Hepatitis B Patients - Yanhua Zheng; Zemin Huang; Xianhua Chen; Yi Tian; Jun Tang; Yi Zhang; Xiaomin Zhang; Jijun Zhou; Qing Mao; Bing Ni; Qinghong Wang; Yuzhang Wu (Mediators of Inflammation)
CD4+ T cells serve as master regulators of the adaptive immune response to HBV. However, CD4+ T-cell subsets are heterogeneous, and it remains unknown how the antiviral agents affect the different CD4+ T cell subtypes. To this end, the expressions of signature transcription factors and cytokines of CD4+ T-cell subtypes were examined in hepatitis B patients before and after treatment with telbivudine. Results showed that, upon the rapid HBV copy decrease induced by telbivudine treatment, the frequencies and related cytokines of Th17 and Treg cells were dramatically decreased, while those for Th2 cells were dramatically increased. No obvious changes were observed in Th1 cell frequencies; although, IFN-γ expression was upregulated in response to telbivudine treatment, suggesting another cell source of IFN-γ in CHB patients. Statistical analyses indicated that Th17 and Tr1 (a Treg subtype) cells were the most sensitive subpopulations of the peripheral blood CD4+ T cells to telbivudine treatment over 52 weeks. Thus, Th17 and Tr1 cells may represent a suitable and effective predictor of responsiveness during telbivudine therapy. These findings not only improve our understanding of hepatitis pathogenesis but also can aid in future development of appropriate therapeutic strategies to control viral hepatitis.